Risk, Regulation and Investor Protection: The Case of Investment Management - Mayer, C; Franks, J (Clarendon Press, 1990)
An authoritative study of the investment management business, focusing on the use of capital requirements for investment managers as a means of investor protection. This report was commissioned by the Investment Management Regulatory Organization.